TINJAUAN TENTANG TANGGUNG JAWAB PERUSAHAAN DAN HAK-HAK KONSUMEN - TRISNOWATI, JUNI (Universitas Surakarta, 2012)
A company is doing business will never be successful if there are no consumers who use their products. In a business relationship between companies and consumers are the responsibility of the company and the rights of consumers to be aware of. Corporate responsibility covers provide a safe product, deliver the product as promised quality, fair prices, and so on. The consumer rights include the right to safety, right to information, right to vote, the right to be heard, the right environment and the right to education. Keywords; corporate responsibility, consumer rights, business relationships.